PENGARUH REPETITIVE TRANSCRANIAL MAGNETIC STIMULATION rTMS TERHADAP INTENSITAS NYERI PENDERITA CENTRAL POSTSTROKE PAIN CPSP - Dody Perdana Goenadhi,* Jumraini Tammasse,* David Gunawan* (Neurona Majalah Kedokteran Neuro Sains, 2018)
INTRODUCTION ABOUT 27 PATIENTS HAVE EXPERIENCED CENTRAL POSTSTROKE PAIN CPSP AFTER STROKE ATTACK REPETITIVE TRANSCRANIAL MAGNETIC STIMULATION RTMS IS A NONPHARMACOLOGICAL METHOD TO OVERCOME CPSP